2014
DOI: 10.1038/npp.2013.351
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Depletion Induces ‘Waiting Impulsivity’ on the Human Four-Choice Serial Reaction Time Task: Cross-Species Translational Significance

Abstract: Convergent results from animal and human studies suggest that reducing serotonin neurotransmission promotes impulsive behavior. Here, serotonin depletion was induced by the dietary tryptophan depletion procedure (TD) in healthy volunteers to examine the role of serotonin in impulsive action and impulsive choice. We used a novel translational analog of a rodent 5-choice serial reaction time task (5-CSRTT)-the human 4-CSRTT-and a reward delay-discounting questionnaire to measure effects on these different forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 45 publications
8
89
1
Order By: Relevance
“…Increased premature responding in BD subjects was accompanied by attentional impairments, revealed as more omitted trials, and lower accuracy of detection in the dual-task condition. Others have recently independently developed a similar human analog of the 5CSRTT to measure waiting impulsivity Worbe et al, 2014), and have found parallels with rodent performance in substance abusers, and following neurochemical manipulations, suggesting close parallels between measures of waiting impulsivity in humans and rodents.…”
Section: Binge Drinking and Human 5csrtt Performancementioning
confidence: 99%
“…Increased premature responding in BD subjects was accompanied by attentional impairments, revealed as more omitted trials, and lower accuracy of detection in the dual-task condition. Others have recently independently developed a similar human analog of the 5CSRTT to measure waiting impulsivity Worbe et al, 2014), and have found parallels with rodent performance in substance abusers, and following neurochemical manipulations, suggesting close parallels between measures of waiting impulsivity in humans and rodents.…”
Section: Binge Drinking and Human 5csrtt Performancementioning
confidence: 99%
“…Earlier findings that global 5-HT depletions with the serotonergic neurotoxin 5,7-dihydroxytryptamine (5,7-DHT) increase impulsivity in rodents measured by increased premature responses on the 5-CSRTT have been translated to humans with 5-HT depletions induced by the dietary tryptophan depletion paradigm in healthy volunteers administered an analogous four-choice serial reaction time test (Harrison et al, 1997;Winstanley et al, 2004;Worbe et al, 2014). Similarly, global brain 5-HT depletions in rats with intraventricular 5,7-DHT lesions also increase the response rate with a clear leftward shift in the IRT distribution in subjects responding under a DRL 72-second schedule (Jolly et al, 1999).…”
Section: Rethinking An Empirical Antidepressant Screenmentioning
confidence: 99%
“…By this means, it has been concluded that central serotonin levels are related to waiting impulsivity rather than stopping impulsivity. Interestingly, it has been determine that tryptophan-depleted individuals had an increase in motivation and accuracy in compliance with individuals who do not have this depletion [53,54].…”
Section: Serotonin On Impulsivitymentioning
confidence: 99%